The Dilemma of Community Security in Iraq after 2003: A Study According to the Propositions of the Copenhagen School - عمارة ياس الزيدي, رشيد; رؤوف سلام, هيمن (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
In today's world, achieving societal security is one of the fundamental duties of states, and internal divisions due to social heterogeneity constitute one of the obstacles to achieving this goal. The Copenhagen School considered this by presenting the concept of the societal security dilemma, which focused on conflicts over identity and internal divisions. In light of that, This study sheds light on the societal security dilemma in Iraq after 2003. The study concludes that the theory of the societal security dilemma advanced by the Copenhagen School is consistent with the analysis of the phenomenon of insecurity in Iraqi society, as Iraqi society consists of multiple religious, national and sectarian groups, which constitute one of the challenges to comprehensive security for the Iraqi society and is dominated by the identity conflict and the dominance of competing will over cooperatively will. This will be examined based on three fundamental requirements: The first section is an introduction to the Copenhagen School and the societal security challenge, while the second part is the relationship between identity and the societal security dilemma in Iraq. Finally, the third section examines the indications and causes of Iraq's social security challenge.